Tahap literasi komputer di kalangan pelajar-pelajar HRD tahun 2 di FSKPM : kajian kes - Hayati, Bujang Zaidon (University Malaysia Sarawak (UNIMAS), 2005)
This research is used to identified students ' level ofcomputer literacy in FSKPM. There are three component of computer literacy involved, attitude toward computers, cognitive knowledge about computer, and skill to operate and use the computer. Questionnaire form was used to get the information for this research from 44 students. The instrument used were ATCS ( Attitude Computer Scale) adopted from Francis, L. J ( 1993 ), MCLAAT ( Minnesota Computer Literacy and Awareness Assessment Test) which was also used by RESCAM ( 1986) and CSES ( Computer Self -Efficiency) which was used by Ridzuan ( 1998 ). Data analysis was done in descriptive and statistic inference ways thqt were Crosstabs using Gjli Square Test and Cramer's V test, t-test and using SPSS version 12. O. The result of the research showed that the student's involve4 gave a positive attitude toward computer where overall min is 3.15. The level of student's cognitive knowledge about computer seem good with its min 0.14 and the scale level which is consider as stable level with significant related with their parent's education but it have a positive relation with the income of theirs parent. The computer literate skill does no also affected by their attitude toward computer. The result showed that the computer literacy level does not give significant differences between gender and the computer they have. Some suggestions are given to improve computer literacy level for the students.